Advanced modelling of a borehole radar environment with the finite difference time domain method - Futter, Peter W. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2001.